Towards a European system of collective redress? - Gascón Inchausti, Fernando (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
The European lawmaker has just approved a new directive on representative actions for the protection of the collective interests of consumers. The road travelled to get here has been arduous and reflects the various drives that are faced in this matter: on the one hand, the assumption that without tools that allow collective redress it will not be possible to achieve the full effectiveness of consumer law; on the other, the fear that European-style collective actions will be used in an abusive way and end up looking too much like American class-actions, with everything associated to them. On this basis, the paper analyses the choices made as to the key elements of the system, such as legal standing, available remedies, access to sources of evidence, the effects of previous final decisions, settlements or funding. Despite the progress, the lawmaker is promoting a very limited harmonization, which casts doubt on the existence of a genuine European model of collective redress.